Spinel-type lithium manganese oxide, its manufacturing method and its use

By surface-modifying spinel-type lithium manganate with phosphate and specific metal elements, the high-temperature stability and output of lithium secondary batteries are enhanced, addressing the limitations of existing spinel-type lithium manganate materials.

JP7647019B2Active Publication Date: 2025-03-18TOSOH CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2020062865
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-03-31
Publication Date
2025-03-18
Estimated Expiration
2040-03-31

AI Technical Summary

Technical Problem

Spinel-type lithium manganate exhibits poor high-temperature stability, particularly in charge and discharge characteristics with carbon counter electrodes, which affects the output and cycle life of lithium secondary batteries.

Method used

The incorporation of phosphate and at least one metal element such as aluminum, magnesium, zinc, nickel, cobalt, iron, or calcium on the surface of spinel-type lithium manganate, forming a chemical formula Li1+X Mn2-X-Y M Y O4, where X and Y are within specific ranges, enhances the high-temperature charge-discharge characteristics.

Benefits of technology

This modification significantly improves the high-temperature charge-discharge characteristics and output of lithium secondary batteries, particularly for carbon counter electrodes, by suppressing manganese elution and maintaining capacity over charge and discharge cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647019000003
    Figure 0007647019000003
  • Figure 0007647019000004
    Figure 0007647019000004
  • Figure 0007647019000005
    Figure 0007647019000005
Patent Text Reader

Abstract

To provide a spinel lithium manganate having excellent charge-discharge properties and output properties at high temperatures and a lithium secondary battery having excellent charge-discharge properties and output properties at high temperatures.SOLUTION: A spinel lithium manganate contains, in its surface, phosphate and at least one metal element of aluminum, magnesium, zinc, nickel, cobalt, iron, and calcium and is represented by chemical formula Li1+XMn2-X-YMgYO4 (in the formula, X and Y are expressed as 0.02≤X≤0.10 and 0.05≤Y≤0.30), with the phosphorus / manganese molar ratio of 0.001 or more and 0.1 or less. There are also provided a method for producing the same and applications thereof.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a spinel-type lithium manganese oxide, a manufacturing method thereof, and uses thereof, and more particularly to a spinel-type lithium manganese oxide having a phosphate attached to its surface, a manufacturing method thereof, and a lithium secondary battery using the same in an electrode. [Background technology]

[0002] Lithium secondary batteries have a higher energy density than other storage batteries, and are therefore widely used as storage batteries for mobile devices. Recently, they have also been applied to large-scale applications that require large capacity and high output, such as stationary and vehicle-mounted applications, and research is ongoing to further improve their performance, including those that have already been put into practical use.

[0003] The positive electrode material of current lithium secondary batteries is mainly cobalt-based material (LiCoO2) for small consumer batteries such as mobile phones, and nickel-based material (LiNi 0.8 Co 0.15 Al 0.05 O2) and nickel-cobalt-manganese ternary materials (LiNi 0.5 Co 0.2 Mn 0.3 O2, etc.) are mainly used. However, cobalt and nickel raw materials are scarce and expensive, and the output characteristics are not very high.

[0004] On the other hand, spinel-type lithium manganese oxide, a manganese-based material, is one of the materials suitable for large batteries and applications requiring high output, because the raw material manganese is abundant and inexpensive, and it also has excellent output characteristics and safety.

[0005] However, spinel-type lithium manganese oxide has a problem in high-temperature stability, that is, in charge / discharge characteristics at high temperatures, particularly in the charge / discharge characteristics and storage characteristics of the carbon counter electrode, and a solution to this problem has been desired. For example, Patent Document 1 and Patent Document 2 both propose spinel-type lithium manganese oxide containing phosphate, but there is still room for improvement in the charge / discharge characteristics at high temperatures, particularly in the charge / discharge characteristics of the carbon counter electrode. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 5556983 [Patent Document 2] JP 2017-31006 A Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a spinel-type lithium manganese oxide having excellent charge / discharge characteristics at high temperatures, particularly excellent carbon counter electrode charge / discharge characteristics and output characteristics, and further to provide a lithium secondary battery using the spinel-type lithium manganese oxide in a positive electrode. [Means for solving the problem]

[0008] The present inventors have conducted extensive research into spinel-type lithium manganese oxide. As a result, they have found that the present invention, which is summarized below, can achieve the above-mentioned object. That is, the present invention relates to a lithium manganese oxide having a surface containing a phosphate and at least one metal element selected from aluminum, magnesium, zinc, nickel, cobalt, iron, and calcium, and having a chemical formula of Li 1+X Mn 2-X-Y Mg YThe present invention relates to a spinel-type lithium manganese oxide having a phosphorus / manganese molar ratio of 0.001 or more and 0.1 or less, and a method for producing the same, and uses thereof. Effect of the Invention

[0009] When the spinel-type lithium manganese oxide of the present invention is used as a positive electrode material for a lithium secondary battery, it is possible to provide a lithium secondary battery that has improved charge / discharge characteristics at high temperatures, particularly the carbon counter electrode charge / discharge characteristics, as well as excellent output characteristics, compared with conventional materials. [Brief description of the drawings]

[0010] [Figure 1] 1 is a SEM-EDX image of the particle surface of the phosphate-containing Mn3O4 obtained in Reference Example 1. [Diagram 2] 1 is an XRD pattern of the phosphate-containing spinel-type lithium manganese oxide obtained in Reference Example 1. [Diagram 3] 1 is a SEM-EDX image of the particle surface of the phosphate-containing spinel-type lithium manganate obtained in Reference Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in detail below.

[0012] The spinel-type lithium manganate of the present invention contains a phosphate and at least one metal element selected from aluminum, magnesium, zinc, nickel, cobalt, iron, and calcium on the surface. By containing a phosphate and at least one metal element selected from aluminum, magnesium, zinc, nickel, cobalt, iron, and calcium on the surface, it is possible to obtain excellent charge-discharge characteristics at high temperatures when used as a positive electrode active material for a lithium secondary battery. At high temperatures, manganese is eluted due to a reaction between hydrogen fluoride contained in a small amount in the electrolyte of the lithium secondary battery and the spinel-type lithium manganate, resulting in a decrease in charge-discharge cycle characteristics. The presence of a phosphate and a metal element on the surface of the spinel-type lithium manganate captures hydrogen fluoride in the electrolyte to suppress manganese elution, making it possible to suppress a decrease in capacity during charge-discharge at high temperatures.

[0013] The spinel-type lithium manganese oxide of the present invention has the chemical formula Li 1+X Mn 2-X-Y Mg Y O4 (wherein X and Y are 0.02≦X≦0.10 and 0.05≦Y≦0.30, respectively). If the value of X is less than 0.02, the capacity is likely to decrease during charging and discharging at high temperatures, and if it exceeds 0.10, sufficient charging and discharging capacity cannot be obtained. If the value of Y is less than 0.05, the capacity is likely to decrease during charging and discharging at high temperatures, and if it exceeds 0.30, sufficient charging and discharging capacity cannot be obtained. X and Y of the spinel-type lithium manganate can be determined by composition analysis. Examples of the method include inductively coupled plasma emission spectrometry and atomic absorption spectrometry.

[0014] The spinel-type lithium manganate of the present invention has a phosphorus / manganese molar ratio of 0.001 or more and 0.1 or less. When the phosphorus / manganese molar ratio is 0.001 or more and 0.1 or less, it is possible to obtain excellent charge / discharge characteristics at high temperatures and increase the charge / discharge capacity when used as a positive electrode active material for a lithium secondary battery. If the phosphorus / manganese molar ratio is less than 0.001, the capacity decrease during charge / discharge at high temperatures tends to be large, which is not preferable. If it is greater than 0.1, the charge / discharge capacity is small, which is not preferable. The phosphorus / manganese molar ratio is preferably 0.001 or more and 0.08 or less, more preferably 0.005 or more and 0.05 or less.

[0015] The spinel-type lithium manganate of the present invention preferably contains at least Li3PO4 as a phosphate. The phosphate used in synthesizing the spinel-type lithium manganate of the present invention is a phosphate containing at least one metal element among aluminum, magnesium, zinc, nickel, cobalt, iron, and calcium, but when the phosphate raw material, manganese raw material, and lithium raw material are mixed and fired, the phosphate and the lithium raw material react to generate Li3PO4. The generated Li3PO4 is present only on the surface of the spinel-type lithium manganate. In addition, the spinel-type lithium manganate of the present invention may have a phosphate containing at least one metal element among aluminum, magnesium, zinc, nickel, cobalt, iron, and calcium other than Li3PO4 on the surface.

[0016] The spinel-type lithium manganese oxide of the present invention, when used as a positive electrode active material for a lithium secondary battery, can provide excellent charge / discharge characteristics at high temperatures and can also provide excellent output characteristics. Therefore, the BET specific surface area of ​​the spinel-type lithium manganese oxide is preferably 0.3 m or less. 2 / g or more 1.5m 2 / g or less, and 0.3m 2 / g or more 0.6m 2 / g or less is more preferable.

[0017] When the spinel-type lithium manganate of the present invention is used as a positive electrode active material for a lithium secondary battery, excellent output characteristics can be obtained, and the filling property of the positive electrode mixture can be enhanced. Therefore, the average particle diameter of the secondary particles is preferably 4 μm or more and 8 μm or less, more preferably 5 μm or more and 7 μm or less.

[0018] When the spinel-type lithium manganate of the present invention is used as a positive electrode active material for a lithium secondary battery, the crystallinity is increased, the elution of manganese is suppressed, the crystal structure change accompanying charge and discharge is suppressed, and excellent charge and discharge characteristics at high temperatures can be obtained. Therefore, the half-value width of the (400) plane by XRD measurement is preferably 0.005 or more and 0.06 or less, more preferably 0.005 or more and 0.05 or less.

[0019] The measurement method of the half-value width was performed by <Measurement of the half-value width by XRD> in the examples. In order to correct the error of the measuring device, after measuring a standard substance in advance, the half-value width of the standard substance was subtracted from the half-value width of the spinel-type lithium manganate to calculate it.

[0020] When the spinel-type lithium manganate of the present invention is used as a positive electrode active material for a lithium secondary battery, the composition is made uniform, and excellent charge and discharge characteristics at high temperatures can be obtained. Therefore, the relative standard deviation of the secondary particle diameter is preferably 60% or less, more preferably 40% or less.

[0021] When the spinel-type lithium manganate of the present invention is used as a positive electrode active material for a lithium secondary battery, excellent charge and discharge characteristics at high temperatures can be obtained. Therefore, the average diameter of the primary particles is preferably 0.5 μm or more and 3.0 μm or less, more preferably 1.0 μm or more and 2.5 μm or less.

[0022] When the spinel-type lithium manganate of the present invention is used as a positive electrode active material for a lithium secondary battery, the charge and discharge capacity is increased, and excellent charge and discharge characteristics at high temperatures can be obtained. Therefore, the content of SO4 is preferably 0.3 wt% or more and 1.0 wt% or less, more preferably 0.4 wt% or more and less than 0.7 wt%.

[0023] In order to increase the crystallinity of the spinel-type lithium manganese oxide of the present invention and obtain excellent charge / discharge characteristics at high temperatures when used as a positive electrode active material for a lithium secondary battery, the Na content is preferably 3,000 wtppm or less, and more preferably 1,000 wtppm or less.

[0024] Next, a method for producing the spinel-type lithium manganese oxide of the present invention will be described.

[0025] The spinel-type lithium manganate of the present invention can be obtained by mixing a manganese raw material containing phosphorus and at least one metal element selected from aluminum, magnesium, zinc, nickel, cobalt, iron, and calcium on the surface, a lithium raw material, and a magnesium raw material, and calcining the mixture at 850 to 950°C in the air or in a high-concentration oxygen atmosphere (including a pure oxygen atmosphere), and then crushing the mixture. Alternatively, the spinel-type lithium manganate can be obtained by mixing a manganese raw material, a lithium raw material, a magnesium raw material, and a phosphoric acid raw material containing at least one metal element selected from aluminum, magnesium, zinc, nickel, cobalt, iron, and calcium phosphates, and then calcining the mixture at 850 to 950°C in the air or in a high-concentration oxygen atmosphere (including a pure oxygen atmosphere), and then crushing the mixture.

[0026] The manganese raw material is not particularly limited, but crystallized Mn3O4, electrolytic MnO2, or Mn2O3 obtained by firing crystallized Mn3O4 or electrolytic MnO2 is preferred because it can improve the packing property when synthesizing spinel-type lithium manganese oxide.

[0027] A manganese raw material containing phosphorus and at least one metal element selected from aluminum, magnesium, zinc, nickel, cobalt, iron, and calcium on the surface thereof can be obtained by preparing a slurry containing crystallized Mn3O4, electrolytic MnO2, or the like, and adding to the slurry an alkaline aqueous phosphate solution and an acidic aqueous solution containing at least one metal element selected from aluminum, magnesium, zinc, nickel, cobalt, iron, and calcium.

[0028] The lithium raw material is not particularly limited, and examples thereof include lithium carbonate, lithium hydroxide, lithium nitrate, lithium chloride, lithium iodide, and lithium oxalate, but are not limited thereto.

[0029] There is no particular limitation on the magnesium raw material, and examples thereof include, but are not limited to, magnesium hydroxide, magnesium oxide, magnesium carbonate, and the like.

[0030] The phosphoric acid raw material containing at least one metal element selected from the group consisting of phosphates of aluminum, magnesium, zinc, nickel, cobalt, iron, and calcium is, for example, AlPO 4、 Al(H2PO4)3, Mg3(PO4)2, Mg(H2PO4)2, Zn3(PO4)2, Ni3(PO4)2, Ni2P2O7, Co3(PO4)2, Fe3(PO4)2, Ca3(PO4) 2、 Examples include CaHPO4, CaH2P2O7, etc.

[0031] Examples of a method for mixing the manganese raw material, the lithium raw material, and the magnesium raw material, or a method for mixing the manganese raw material, the lithium raw material, the magnesium raw material, and the phosphoric acid raw material include dry mixing and wet mixing.

[0032] The calcination for obtaining the spinel-type lithium manganate of the present invention is carried out in air or in a high-concentration oxygen atmosphere (including a pure oxygen atmosphere), i.e., in an oxygen atmosphere with an oxygen content of 18 to 100 vol%, at 850 to 950°C. At temperatures lower than 850°C, the BET specific surface area of ​​the spinel-type lithium manganate tends to increase, while at temperatures exceeding 950°C, the oxygen deficiency of the spinel-type lithium manganate increases, and as a result, the charge-discharge cycle characteristics tend to decrease when used as a positive electrode active material for a lithium secondary battery. The calcination is preferably carried out at 900 to 930°C.

[0033] Since the secondary particles of spinel-type lithium manganate tend to agglomerate during firing, the material is crushed to obtain the desired particle size. The crushing method is preferably by shear force to suppress the generation of fine powder and the increase in the BET specific surface area.

[0034] After crushing the spinel-type lithium manganese oxide, it is preferable to pass it through a sieve with an opening of 50 μm or less in order to remove coarse particles that exceed the thickness of the positive electrode.

[0035] By using the phosphate-containing spinel-type lithium manganese oxide of the present invention in the positive electrode of a lithium secondary battery, it is possible to configure a lithium secondary battery that has excellent charge / discharge cycle characteristics at high temperatures and excellent output characteristics, which were not previously possible.

[0036] The composition of the lithium secondary battery other than the positive electrode is not particularly limited. However, the negative electrode is preferably made of a material that absorbs and releases Li, such as a carbon-based material, a tin oxide-based material, or Li4Ti5O 12 , SiO, and materials that form an alloy with Li. Examples of materials that form an alloy with Li include silicon-based materials and aluminum-based materials. Examples of electrolytes include organic electrolytic solutions in which Li salts and various additives are dissolved in an organic solvent, Li-ion conductive solid electrolytes, and combinations of these. EXAMPLES

[0037] Next, the present invention will be described with reference to specific examples, but the present invention is not to be construed as being limited to these examples.

[0038] <Battery performance test> (1) Initial capacity measurement, lithium counter electrode charge / discharge cycle test 25 mg of the spinel-type lithium manganate obtained in each Example was mixed with 12.5 mg of a conductive binder (product name: TAB-2, manufactured by Hosen) using an agate mortar. The resulting mixture was applied to a SUS mesh (SUS316) with a diameter of 16 mm at a rate of 2 ton / cm. 2 The mixture was uniaxially pressed at 80° C. to form a disk-shaped pellet, which was then dried under reduced pressure at 150° C. for 2 hours to form a positive electrode.

[0039] Metallic lithium was used for the negative electrode, and LiPF6 was added at 1 mol / dm in a solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:2. 3 The dissolved material was used as the electrolyte, a polyethylene sheet (product name: Celgard, manufactured by Polypore) was used as the separator, and a model cell (product name: Tomcell, manufactured by Tomcell Japan, Ltd.) was used as the cell to fabricate a battery.

[0040] The fabricated battery was used to measure the current density of 0.4 mA / cm at a cell voltage between 4.3 V and 3.0 V at 60°C. 2 The battery was charged and discharged for one cycle at a constant current of 1.3 mA / cm at 60°C, with the cell voltage between 4.3 V and 3.0 V, and the charge capacity at the first cycle was taken as the initial capacity. 2 The battery was charged and discharged 50 times at a constant current, and the charge-discharge cycle characteristics of the lithium counter electrode were determined from the ratio of the discharge capacity at the 50th cycle to that at the 1st cycle.

[0041] (2) Carbon counter electrode charge / discharge cycle test The negative electrode was a spherulitic graphite sheet (Hosen TSG-A1, nominal capacity 1.6 mAh / cm 2 ) was punched to a diameter of 16.156 mm and then subjected to a pressure of 3 ton / cm 2 The batteries were fabricated in the same manner as in the lithium counter electrode charge-discharge cycle test, except that the batteries used were uniaxially pressed at 1000 K, the amount of positive electrode active material was adjusted so that the negative electrode / positive electrode capacity ratio was 1.2, a polypropylene gasket was used, and a CR2032 coin cell was used.

[0042] Using the fabricated battery, the current density was 0.14 mA / cm at a cell voltage between 4.25 V and 3.0 V at 24°C. 2 The battery was then subjected to one cycle of constant current / constant voltage charge / constant current discharge at 24°C, with the cell voltage between 4.25 V and 3.0 V, and a current density of 0.28 mA / cm 2One cycle of constant current / constant voltage charge / constant current discharge was performed at 60°C, with the cell voltage between 4.25V and 3.0V, and the discharge capacity was taken as the battery capacity. Next, 50 cycles of constant current / constant voltage charge / constant current discharge were performed at a current density of 1-hour discharge rate for the battery capacity at 60°C, with the cell voltage between 4.25V and 3.0V, and the carbon counter electrode charge / discharge cycle characteristics were calculated from the ratio of the discharge capacity at the 50th cycle to the 1st cycle. The constant voltage charge was terminated when the charge current was attenuated to 1 / 10 of that at the constant voltage charge.

[0043] (3) Output characteristics test A battery was fabricated in the same manner as in the lithium counter electrode charge-discharge cycle test, except that the amount of spinel-type lithium manganate was 10 mg and the amount of conductive binder (product name: TAB-2, manufactured by Hohsen) was 10 mg.

[0044] The fabricated battery was used at 24°C, with a cell voltage between 4.3 V and 3.0 V and a current density of 0.15 mA / cm 2 After three cycles of charge and discharge at a constant current of 0.15 mA / cm 2 , discharge current 5mA / cm 2 The battery was charged and discharged three times at a constant current of 5mA / cm 2 Discharge capacity at the third cycle and current density at 0.15mA / cm 2 The output characteristics were calculated from the ratio of the discharge capacity in the third cycle.

[0045] <Composition analysis, SO4 content, Na content measurement> The composition, phosphorus / manganese molar ratio, SO content, and Na content of the spinel-type lithium manganate prepared in the examples and comparative examples were analyzed by dissolving the spinel-type lithium manganate in a mixed aqueous solution of hydrochloric acid and hydrogen peroxide, and then using an inductively coupled plasma atomic emission spectrometer (product name: ICP-AES, manufactured by PerkinElmer Japan).

[0046] <Measurement of the distribution of phosphorus and metal elements and the average particle size of lithium manganate primary particles> For the spinel-type lithium manganate prepared in the examples and comparative examples, the distribution states of phosphorus and metal elements and the measurement of the average particle diameter of primary particles were carried out with a scanning electron microscope (trade name: JSM-IT500, manufactured by JEOL Ltd.).

[0047] <Measurement of the half-value width by XRD> For the spinel-type lithium manganate prepared in the examples and comparative examples, the measurement of the half-value width by XRD was carried out with a powder XRD measuring apparatus (trade name: Ultima IV, manufactured by Rigaku Corporation). The measurement conditions were as follows.

[0048] · Target: Cu · Output: 1.6 kW (40 mA - 40 kV) · Filter: Kβ filter · Divergence slit: 1° · Divergence vertical limiting slit: 10 mm · Scattering slit: Open · Receiving slit; Open · Scanning mode: Continuous · Scan speed: 4.000° / min · Sampling width: 0.04° (2θ / θ) · Integration times: 1 time · Measurement range: 10 - 90° (2θ / θ) The obtained XRD data of the spinel-type lithium manganate were analyzed using the analysis software (PDXL2) attached to the powder X-ray diffractometer, and the integral width of the (400) plane near 2θ = 44° was determined.

[0049] Also, in order to correct the error of the measuring apparatus, the measurement of the XRD standard substance (α-type quartz powder manufactured by NIST) was carried out in advance, and the half-value width was obtained by subtracting the integral width of the standard substance from the integral width of the spinel-type lithium manganate.

[0050] <Measurement of BET specific surface area> 1.0 g of the sample was placed in a glass cell for measuring the BET specific surface area, and dehydration treatment was carried out at 150 °C for 30 minutes under a nitrogen stream to remove the moisture adhering to the powder particles.

[0051] The BET specific surface area of ​​the treated sample was measured by a single-point method using a BET measuring device (product name: MiCROMERITICS DeSorbIII, manufactured by Shimadzu Corporation) with a mixed gas of 30% nitrogen and 70% helium as the adsorption gas.

[0052] <Measurement of the average particle size and relative standard deviation of secondary particles of lithium manganate> The average particle diameter (D 50 ) and the standard deviation of particle size were measured.

[0053] From the measured average particle size and standard deviation of the secondary particles, the relative standard deviation of the secondary particle size was calculated according to the following formula.

[0054] Relative standard deviation (%) = (Standard deviation of particle size) / (Average particle size) x 100 Reference example 1 Pure water at 60°C was stirred while air was blown into it. A 2 mol / L manganese sulfate aqueous solution and a 20 wt% sodium hydroxide aqueous solution were continuously added to the pure water while the oxidation-reduction potential of the pure water was kept constant at 100 mV based on the hydrogen electrode standard, and the resulting slurry was filtered, washed, and dried to obtain Mn3O4 with an average particle size of 3.8 μm.

[0055] A slurry was prepared by adding 2.5 L of pure water to 100 g of Mn3O4, and then 300 g of 7.8 mmol / kg aluminum sulfate and 300 g of 31.3 mmol / kg diammonium phosphate were added continuously over 5 hours while stirring at 23°C. The slurry was then filtered, washed with water, and dried at 110°C. The aluminum / manganese molar ratio and phosphorus / manganese molar ratio of the obtained material were both 0.0038. The SEM-EDS image of the particle surface is shown in Figure 1. From the SEM-EDS image, it was observed that aluminum and phosphorus were uniformly present on the particle surface. In addition, only Mn3O4 No. 24-734 of JCPDS was observed in the XRD pattern. Therefore, the obtained material was considered to be Mn3O4 with amorphous aluminum phosphate uniformly supported on the surface.

[0056] 78.00g of aluminum phosphate-supported Mn3O4, 22.00g of Li2CO3 with an average particle size of 3μm, and 1.77g of Mg(OH)2 (manufactured by Wako Pure Chemical Industries, average particle size 0.07μm) were mixed in a dry state, and fired at 900°C for 6 hours in a box furnace while circulating air at a rate of 5L / min, and cooled to room temperature. The heating rate was 100°C / hr, and the heating rate was 20°C / hr from 900°C to 600°C, and 100°C / hr from 600°C to room temperature. The obtained phosphate-containing spinel-type lithium manganate was crushed with a powerful small crusher (trade name: Force Mill, manufactured by Osaka Chemical) to obtain phosphate-containing spinel-type lithium manganate.

[0057] The composition of the obtained phosphate-containing spinel-type lithium manganese oxide was Li 1.08 Mn 1.86 Mg 0.06O4. The XRD pattern of the obtained phosphate-containing spinel-type lithium manganate is shown in Figure 2. The XRD pattern was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). The SEM-EDS image of the surface of the phosphate-containing spinel-type lithium manganate particles is shown in Figure 3. Aluminum and phosphorus were observed on the surface. The phosphorus / manganese molar ratio, BET specific surface area, average particle size of lithium manganate secondary particles, half-width of the (400) plane by XRD measurement, relative standard deviation of secondary particle size, average particle size of lithium manganate primary particles, SO4 content, and Na content are shown in Table 1, and the battery performance is shown in Table 2.

[0058] [Table 1]

[0059] [Table 2]

[0060] Example 2 A phosphate-containing spinel-type lithium manganate was obtained in the same manner as in Reference Example 1, except that the concentration of aluminum sulfate was 15.6 mmol / kg, the concentration of diammonium phosphate was 62.6 mmol / kg, and the amount of Li2CO3 mixed was 22.17 g.

[0061] The composition of the obtained phosphate-containing spinel-type lithium manganese oxide was Li 1.07 Mn 1.87 Mg 0.06O4. XRD measurements showed that the obtained phosphate-containing spinel-type lithium manganate was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). SEM-EDS measurements of the surface of the phosphate-containing spinel-type lithium manganate particles showed that aluminum and phosphorus were observed on the particle surface. Table 1 shows the phosphorus / manganese molar ratio, BET specific surface area, average particle size of lithium manganate secondary particles, half-width of the (400) plane by XRD measurement, relative standard deviation of secondary particle size, average particle size of lithium manganate primary particles, SO4 content, and Na content, and Table 2 shows the battery performance.

[0062] Example 3 A phosphate-containing lithium manganese spinel-type oxide was obtained in the same manner as in Example 2, except that the firing temperature was 930°C.

[0063] The composition of the obtained phosphate-containing spinel-type lithium manganese oxide was Li 1.07 Mn 1.87 Mg 0.06 O4. XRD measurements showed that the obtained phosphate-containing spinel-type lithium manganate was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). SEM-EDS measurements of the surface of the phosphate-containing spinel-type lithium manganate particles showed that aluminum and phosphorus were observed on the particle surface. Table 1 shows the phosphorus / manganese molar ratio, BET specific surface area, average particle size of lithium manganate secondary particles, half-width of the (400) plane by XRD measurement, relative standard deviation of secondary particle size, average particle size of lithium manganate primary particles, SO4 content, and Na content, and Table 2 shows the battery performance.

[0064] Reference example 2 The aluminum sulfate concentration was 3.9 mmol / kg, the diammonium phosphate concentration was 15.7 mmol / kg, the amount of Li2CO3 mixed was 22.23 g, and the firing temperature was 930°C. Reference example 1 A phosphate-containing spinel-type lithium manganese oxide was obtained in the same manner as described above.

[0065] The composition of the obtained phosphate-containing spinel-type lithium manganese oxide was Li 1.09 Mn 1.85 Mg 0.06 O4. XRD measurements showed that the obtained phosphate-containing spinel-type lithium manganate was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). SEM-EDS measurements of the surface of the phosphate-containing spinel-type lithium manganate particles showed that aluminum and phosphorus were observed on the particle surface. Table 1 shows the phosphorus / manganese molar ratio, BET specific surface area, average particle size of lithium manganate secondary particles, half-width of the (400) plane by XRD measurement, relative standard deviation of secondary particle size, average particle size of lithium manganate primary particles, SO4 content, and Na content, and Table 2 shows the battery performance.

[0066] Example 5 Pure water at 60°C was stirred while air was blown into it. A 2 mol / L manganese sulfate aqueous solution and a 20 wt% sodium hydroxide aqueous solution were continuously added to the pure water while the oxidation-reduction potential of the pure water was kept constant at 100 mV based on the hydrogen electrode standard, and the resulting slurry was filtered, washed, and dried to obtain Mn3O4 with an average particle size of 3.8 μm.

[0067] 78.00g of Mn3O4, 22.18g of Li2CO3 with an average particle size of 3μm, 1.77g of Mg(OH)2 (manufactured by Wako Pure Chemical Industries, average particle size 0.07μm), and 1.61g of Mg3(PO4)2·8H2O (manufactured by Kishida Chemical) were mixed in a dry state, and the mixture was fired at 900℃ for 6 hours in a box furnace while circulating air at a rate of 5L / min, and then cooled to room temperature. The heating rate was 100℃ / hr, and the cooling rate was 20℃ / hr from 900℃ to 600℃, and 100℃ / hr from 600℃ to room temperature. The obtained phosphate-containing spinel-type lithium manganese oxide was crushed with a powerful small crusher (trade name: Force Mill, manufactured by Osaka Chemical) to obtain phosphate-containing spinel-type lithium manganese oxide.

[0068] The composition of the obtained phosphate-containing spinel-type lithium manganese oxide was Li1.06 Mn 1.87 Mg 0.07 O4. XRD measurements showed that the obtained phosphate-containing spinel-type lithium manganate was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). SEM-EDS measurements of the surface of the phosphate-containing spinel-type lithium manganate particles showed that magnesium and phosphorus were observed on the particle surface. Table 1 shows the phosphorus / manganese molar ratio, BET specific surface area, average particle size of lithium manganate secondary particles, half-width of the (400) plane by XRD measurement, relative standard deviation of secondary particle size, average particle size of lithium manganate primary particles, SO4 content, and Na content, and Table 2 shows the battery performance.

[0069] Example 6 A phosphate-containing spinel-type lithium manganese oxide was obtained in the same manner as in Example 5, except that the amount of Li2CO3 mixed was 22.44 g and 1.82 g of Zn3(PO4)2·4H2O (Kishida Chemical) was used as the phosphate.

[0070] The composition of the obtained phosphate-containing spinel-type lithium manganese oxide was Li 1.08 Mn 1.86 Mg 0.06 O4. XRD measurements showed that the obtained phosphate-containing spinel-type lithium manganate was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). SEM-EDS measurements of the surface of the phosphate-containing spinel-type lithium manganate particles showed that zinc and phosphorus were observed on the particle surface. Table 1 shows the phosphorus / manganese molar ratio, BET specific surface area, average particle size of lithium manganate secondary particles, half-width of the (400) plane by XRD measurement, relative standard deviation of secondary particle size, average particle size of lithium manganate primary particles, SO4 content, and Na content, and Table 2 shows the battery performance.

[0071] Example 7 A phosphate-containing spinel-type lithium manganese oxide was obtained in the same manner as in Example 5, except that the amount of Li2CO3 mixed was 22.36 g and an aqueous solution of 1.14 g of Mg(H2PO4)2·4H2O (manufactured by Junsei Chemical Co., Ltd.) dissolved in 5 g of pure water was used as the phosphate.

[0072] The composition of the obtained phosphate-containing spinel-type lithium manganese oxide was Li 1.06 Mn 1.87 Mg 0.07 O4. XRD measurements showed that the obtained phosphate-containing spinel-type lithium manganate was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). SEM-EDS measurements of the surface of the phosphate-containing spinel-type lithium manganate particles showed that magnesium and phosphorus were observed on the particle surface. Table 1 shows the phosphorus / manganese molar ratio, BET specific surface area, average particle size of lithium manganate secondary particles, half-width of the (400) plane by XRD measurement, relative standard deviation of secondary particle size, average particle size of lithium manganate primary particles, SO4 content, and Na content, and Table 2 shows the battery performance.

[0073] Example 8 A phosphate-containing spinel-type lithium manganese oxide was obtained in the same manner as in Example 5, except that the amount of Li2CO3 mixed was 22.36 g, 0.83 g of Al(H2PO4)3 (manufactured by Junsei Chemical Co., Ltd.) was used as the phosphate, and the firing temperature was 930°C.

[0074] The composition of the obtained phosphate-containing spinel-type lithium manganese oxide was Li 1.07 Mn 1.87 Mg 0.06O4. XRD measurements showed that the obtained phosphate-containing spinel-type lithium manganate was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). SEM-EDS measurements of the surface of the phosphate-containing spinel-type lithium manganate particles showed that aluminum and phosphorus were observed on the particle surface. Table 1 shows the phosphorus / manganese molar ratio, BET specific surface area, average particle size of lithium manganate secondary particles, half-width of the (400) plane by XRD measurement, relative standard deviation of secondary particle size, average particle size of lithium manganate primary particles, SO4 content, and Na content, and Table 2 shows the battery performance.

[0075] Example 9 A phosphate-containing spinel-type lithium manganate was obtained in the same manner as in Example 5, except that the amount of Li2CO3 mixed was 22.18 g and 1.33 g of CaHPO4·2H2O (manufactured by Wako Pure Chemical Industries, Ltd.) was used as the phosphate.

[0076] The composition of the obtained phosphate-containing spinel-type lithium manganese oxide was Li 1.08 Mn 1.86 Mg 0.06 O4. XRD measurement showed that the obtained phosphate-containing spinel-type lithium manganate was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). SEM-EDS measurement of the surface of the phosphate-containing spinel-type lithium manganate particles showed that calcium and phosphorus were observed on the particle surface. The phosphorus / manganese molar ratio, BET specific surface area, average particle size of lithium manganate secondary particles, half-width of the (400) plane by XRD measurement, relative standard deviation of secondary particle size, average particle size of lithium manganate primary particles, SO4 content, and Na content are shown in Table 1, and the battery performance is shown in Table 2.

[0077] Example 10 A phosphate-containing spinel-type lithium manganate was obtained in the same manner as in Example 5, except that the amount of Li2CO3 mixed was 22.44 g and 0.86 g of CaH2P2O7 (manufactured by Wako Pure Chemical Industries, Ltd.) was used as the phosphate.

[0078] The composition of the obtained phosphate-containing spinel-type lithium manganese oxide was Li 1.08 Mn 1.86 Mg 0.06 O4. XRD measurement showed that the obtained phosphate-containing spinel-type lithium manganate was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). SEM-EDS measurement of the surface of the phosphate-containing spinel-type lithium manganate particles showed that calcium and phosphorus were observed on the particle surface. The phosphorus / manganese molar ratio, BET specific surface area, average particle size of lithium manganate secondary particles, half-width of the (400) plane by XRD measurement, relative standard deviation of secondary particle size, average particle size of lithium manganate primary particles, SO4 content, and Na content are shown in Table 1, and the battery performance is shown in Table 2.

[0079] Example 11 A phosphate-containing spinel-type lithium manganate was obtained in the same manner as in Example 5, except that the amount of Li2CO3 mixed was 22.18 g and 2.11 g of Co3(PO4)2·8H2O (manufactured by Wako Pure Chemical Industries, Ltd.) was used as the phosphate.

[0080] The composition of the obtained phosphate-containing spinel-type lithium manganese oxide was Li 1.10 Mn 1.84 Mg 0.06 O4. XRD measurements showed that the obtained phosphate-containing spinel-type lithium manganate was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). SEM-EDS measurements of the surface of the phosphate-containing spinel-type lithium manganate particles showed that cobalt and phosphorus were observed on the particle surface. The phosphorus / manganese molar ratio, BET specific surface area, average particle size of lithium manganate secondary particles, half-width of the (400) plane by XRD measurements, relative standard deviation of secondary particle size, average particle size of lithium manganate primary particles, SO4 content, and Na content are shown in Table 1, and the battery performance is shown in Table 2.

[0081] Example 12 A phosphate-containing spinel-type lithium manganate was obtained in the same manner as in Example 5, except that the amount of Li2CO3 mixed was 22.20 g and 1.60 g of Ni2P2O7·7H2O (manufactured by Wako Pure Chemical Industries, Ltd.) was used as the phosphate.

[0082] The composition of the obtained phosphate-containing spinel-type lithium manganese oxide was Li 1.10 Mn 1.84 Mg 0.06 O4. XRD measurement showed that the obtained phosphate-containing spinel-type lithium manganate was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). SEM-EDS measurement of the surface of the phosphate-containing spinel-type lithium manganate particles showed that nickel and phosphorus were observed on the particle surface. Table 1 shows the phosphorus / manganese molar ratio, BET specific surface area, average particle size of lithium manganate secondary particles, half-width of the (400) plane by XRD measurement, relative standard deviation of secondary particle size, average particle size of lithium manganate primary particles, SO4 content, and Na content, and Table 2 shows the battery performance.

[0083] Comparative Example 1 A spinel-type lithium manganate was obtained in the same manner as in Example 5, except that no phosphate was added and the amount of Li2CO3 mixed was 21.21 g.

[0084] The composition of the obtained spinel-type lithium manganese oxide was Li 1.07 Mn 1.87 Mg 0.06 O4. Furthermore, from the XRD measurement, the obtained spinel type lithium manganate was JCPDS No. 35-782 (LiMn2O4) single phase. The phosphorus / manganese molar ratio, BET specific surface area, average particle size of lithium manganate secondary particles, half width of (400) plane by XRD measurement, relative standard deviation of secondary particle size, average particle size of lithium manganate primary particles, SO4 content, and Na content are shown in Table 1, and the battery performance is shown in Table 2. From Table 2, it is clear that the carbon counter electrode cycle characteristics of Comparative Example 1 are inferior to those of the Examples. [Industrial Applicability]

[0085] The phosphate-containing spinel-type lithium manganese oxide of the present invention contains a specific phosphate and at least one metal element selected from aluminum, magnesium, zinc, nickel, cobalt, iron and calcium, and has a half-width, BET specific surface area and secondary particle size as measured by XRD. Therefore, it has excellent charge / discharge characteristics at high temperatures, in particular carbon counter electrode charge / discharge characteristics, and can be used as a positive electrode active material for a lithium secondary battery having excellent output characteristics.

Claims

1. The surface of the catalyst contains phosphate and at least one metal element selected from aluminum, magnesium, zinc, nickel, cobalt, iron, and calcium, and has the chemical formula Li 1+X Mn 2-X-Y Mg Y O 4 (wherein X and Y are each represented by 0.02≦X≦0.10 and 0.05≦Y≦0.30, respectively), and characterized in that the phosphorus / manganese molar ratio is 0.0074 or more and 0.0080 or less.

2. At least Li as phosphate 3 P.O. 4 2. The spinel-type lithium manganese oxide according to claim 1, further comprising:

3. BET specific surface area is 0.3m 2 / g or more 1.5m 2 3. The spinel-type lithium manganate according to claim 1, wherein the lithium manganese oxide has a molecular weight of 1.0 to 1.0 g / g or less.

4. 4. The spinel-type lithium manganate according to claim 1, wherein the average particle size of the secondary particles is 4 μm or more and 8 μm or less.

5. 5. The spinel-type lithium manganate according to claim 1, wherein the half-value width of the (400) plane as measured by XRD is 0.005 or more and 0.06 or less.

6. 6. The spinel-type lithium manganese oxide according to claim 1, wherein the relative standard deviation of the secondary particle diameter is 60% or less.

7. 7. The spinel-type lithium manganate according to claim 1, wherein the average diameter of primary particles as determined by SEM observation is 0.5 μm or more and 3.0 μm or less.

8. SO 4 The spinel-type lithium manganese oxide according to any one of claims 1 to 7, characterized in that the content of is 0.3 wt % or more and 1.0 wt % or less.

9. 9. The spinel-type lithium manganate according to claim 1, wherein the Na content is 3,000 wtppm or less.

10. The method for producing spinel-type lithium manganate according to any one of claims 1 to 9, characterized in that a manganese raw material containing phosphorus and at least one metal element selected from aluminum, magnesium, zinc, nickel, cobalt, iron and calcium on a surface thereof, a lithium raw material and a magnesium raw material are mixed, and the mixture is fired at 850 to 950°C in air or in a high-concentration oxygen atmosphere (including a pure oxygen atmosphere), and then crushed.

11. 10. The method for producing spinel-type lithium manganate according to any one of claims 1 to 9, characterized in that a manganese raw material, a lithium raw material, a magnesium raw material, and a phosphate raw material containing at least one metal element selected from the group consisting of phosphates of aluminum, magnesium, zinc, nickel, cobalt, iron, and calcium are mixed together, and the mixture is fired at 850 to 950°C in air or in a high-concentration oxygen atmosphere (including a pure oxygen atmosphere), and then crushed.

12. The method for producing spinel-type lithium manganese oxide according to claim 11, characterized in that the average particle size of the phosphoric acid raw material is 5 μm or less.

13. The method for producing spinel-type lithium manganese oxide according to claim 11, characterized in that an aqueous solution of a phosphate is used as a raw material.

14. An electrode comprising the spinel-type lithium manganese oxide according to any one of claims 1 to 9.

15. A lithium secondary battery using the electrode according to claim 14 as a positive electrode.

Citation Information

Patent Citations

  • Latch mechanism for spreader

    JP1980056983A

  • Lithium manganate for nonaqueous electrolyte secondary battery and its manufacturing method, and nonaqueous electrolyte secondary battery

    JP2009176732A

  • Lithium manganese composite oxide powder and production method therefor

    JP2017031006A